Organizational identities and institutions: Dynamics of the organizational core as a question of path dependence - Stefan Kirchner (Max Planck Institute for the Study of Societies, 2010)
Organizational identity is a mechanism that mediates between external pressures and internal demands on continuity. The concept of organizational identity is considered to be central to solving the research problem addressed of combining the effects of an institutional environment with the continuity of organizational core structures. In the course of feedback processes between organizational identity and activities, a path dependent development of organizational identity can be triggered. In this situation, organizations are restrained in their ability to adapt core structures to changing environmental conditions. – – Die Organisationsidentität beschreibt einen Mechanismus, der zwischen externem Druck und internen Anforderungen an Kontinuität vermittelt. Das Konzept der Organisationsidentität wird als zentral angesehen, um die gestellte Forschungsfrage nach der Verbindung zwischen institutioneller Umwelt und der Kontinuität von Kernbestandteilen der Organisation zu klären. Infolge von Feedbackprozessen zwischen der Organisationsidentität und den Aktivitäten in einer Organisation kann eine pfadabhängige Entwicklung der Organisationsidentität ausgelöst werden. In einer solchen Situation sind Organisationen erheblich in ihrer Fähigkeit beeinträchtigt, Kernbestandteile an veränderte Umweltbedingungen anzupassen.
Keywords: 300; Unternehmenskultur; Institutioneller Wandel; Pfadabhängigkeit